Simulated annealing ray tracing in complex 3-D media - Velis, Danilo Rubén (2001)
Simulated annealing has been applied to seismic ray tracing to determine the minimum traveltime ray path connecting two points in complex 3-D media. In contrast to conventional ray tracing schemes such as shooting and bending, simulated annealing ray tracing (SART) overcomes some well-known difficulties regarding multipathing and take-off angle selection. These include local convergence (that is, failing to obtain the ray path with absolute minimum traveltime) and divergence of the take-off angle selection strategy. Under these circumstances, shooting and bending methods may not provide reliable results in highly variable 3-D media. A flexible model representation is used to accommodate a large class of velocity models.